2013
DOI: 10.19026/rjaset.6.3797
|View full text |Cite
|
Sign up to set email alerts
|

Fuel Consumption Evaluation of Some Commonly Used Farm Tractors for Ploughing Operations on the Sandy-loam soil of Oyo State, Nigeria

Abstract: Farm Tractors acquired in Oyo State-Nigeria are primarily utilized for ploughing operations which represents the most costly single item in the budget of an arable farmer. Tractor fuel consumption constitutes a significant parameter that affects ploughing operations performances. Ploughing operations, using ASABE standard D 497.5 were carried out using Massey Ferguson ( MF 435, 100 hp), Fiat ( F130D, 100 hp) and Steyr ( CVT170, 100 hp) tractors that were purchased in 2009. Field experiments were conducted at 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 6 publications
1
6
0
Order By: Relevance
“…Deeper tillage with mouldboard plow as shown in Table 1 was another significant reason of rising fuel consumption. This could be supported with the findings of Fathollahzadeh et al (2010), Namdari et al (2011) and Adewoyin (2013). They determined that fuel consumption increased due to increased plowing depth.…”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…Deeper tillage with mouldboard plow as shown in Table 1 was another significant reason of rising fuel consumption. This could be supported with the findings of Fathollahzadeh et al (2010), Namdari et al (2011) and Adewoyin (2013). They determined that fuel consumption increased due to increased plowing depth.…”
Section: Resultssupporting
confidence: 82%
“…Although a mouldboard plow used in conventional tillage practices can, under some conditions, provide protection from weed infestation (Calado et al 2013), conventional tillage with a plow is one of the processes with high fuel consumption (Moitzi et al 2014). Deeper tillage with a mouldboard plow is a significant reason for rising fuel consumption (Adewoyin 2013;Fathollahzadeh et al 2010;Namdari et al 2011). Many studies about the fuel consumption of tillage practices showed that conventional tillage with a mouldboard plow resulted in higher fuel consumption compared with conservation (reduced and no-tillage) practices (Akbarnia and Farhani 2014;Alamouti and Mohammadi 2015;Filipović et al 2004;Sarauskis et al 2012;Yalcin et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Limited power and range: Solar-powered machinery may have limited power and range compared to traditional fossil fuel-powered equipment, particularly for heavy-duty tasks such as tillage or harvesting [84]. This can limit their usefulness for some farming operations or require the use of hybrid systems that combine solar power with other energy sources [85].…”
Section: Solar-powered Farm Machinerymentioning
confidence: 99%
“…When the interrogator of the proposed system moves with a farm machinery, the speed of the farm machinery is one of primary factors which affects the system performance in harvesting energy. Farming tractors typically run at the speeds ranging from 5.5 to 7.5 Kilometres Per Hour (kph) [101]. With the speeds in that range, the on-vehicle interrogator can easily travel more than 1.5 metres per second.…”
Section: The System Is Compatible With Modern Farming Practicementioning
confidence: 99%
“…In practice, a tractor typically runs at a speed of 5.5 Kilometres Per Hour (kph) for ploughing operations [101]. According to Equation 11.7, the calculated powering time that is provided at the typical tractor speed is 0.8 s. The calculation is based on one of the realistic scenarios where the reader antenna height is 0.5 m, the depth of the sensor node is 0.4 m, and the beamwidth of the reader antenna, θ, is 70 degrees [138].…”
Section: Tractor Speedmentioning
confidence: 99%